DEVELOPING HOCKEY GAME FOR LEARNING MEDIA OF PHYSICAL EDUCATION SPORT AND HEALTH TO JUNIOR HIGH SCHOOL STUDENTS (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
The goal of this developing research were : 1) Generate a hockey game which appropriate for the learning media of physical education sport and health to junior high school students. 2) Determine the effectiveness of hockey game that was developed for learning of physical education sport and health to junior high school students, 3) Determine acceptance model hockey games in the learning process. The developing research model which used was procedural development. The procedure used consists of five main stages: 1) to analyze the product to be developed, 2) develop the initial product model for junior hockey games, 3) validation experts, 4) field trials and 5) revision of the product. Subjects who used the VII grade students of State Junior High School 1 Semarang and State Junior High School 23 Semarang, amounting to 96 students consisting of 41 boys and 55 girls students. The data used were qualitative and quantitative data. Technical analysis was the percentage used to analyze and assess the level of assessment of the subjects in the feasibility, quality and product acceptance. The study produced a model for learning physical education sport and health of hockey in junior high school students in the city, with developing the infrastructure that includes extensive field 28 meters x 14 meters, the ball used is a hockey ball, the size of the wicket with a length of 1 meter high and 0.4 meters, hitter (stick) made of wooden boards (mahogany) with a length of 0.92 meters. For the regulation number of players per team game consists of 12 players with 6 core players and 6 players without the goal keeper, game time is 10 minutes, the team who wins was the team that can goals at most compared to the opposing team. Where these results were packaged in a book and learning vcd. Based on the research results could be summarized as follows: 1) The form of this hockey game development in accordance with the learning media of physical education sport and health, 2) model developed hockey games are also very effective for learning media of physical education sport and health, 3) hockey game that was developed model can be accepted and implemented in the learning process of physical education sport and health in junior high school. Teachers physical education sport and health was advised to use this game model as an alternative way to delivery little ball game learning lesson for junior high school students. The product of this game can be harnessed for the media to learn the motion for junior high students. The results of this research can be the basement of the next research